PENGARUH PROFESIONALISME GURU TERHADAP PRESTASI BELAJAR SISWA PADA SEKOLAH MENENGAH PERTAMA (SMP) YAPIS MERAUKE - Indriaty, Lulu; Ansar, Ansar (DINAMIS, 2020)
This study is entitled The Effect of Teacher Professionalism on Student Learning Achievement in Yapis Merauke Middle School (SMP). This study aims to find out how much the influence of teacher professionalism on student achievement both simultaneously and partially.The study population is the total number of teachers in the Yapis Merauke junior high school as many as 35 people.The results of the multiple linear regression equation are: Y = 15.147 + 0.076X₁ + 0.096X₂ + 0.088X₃. While the results of the study showed that the variables of teacher professionalism, namely education, experience and attitude simultaneously had a positive and significant effect on student achievement in Yapis Merauke junior high school with a Fcount value of 7.583, a significant level of 0.000, while a Ftable value with an alpha of 0.05 was obtained value of 2,679. Education has an influence on student achievement in junior high school (SMP) Yapis Merauke with a tcount of 2,563 and a sig of 0,000. Experience has an influence on student achievement in junior high school (SMP) Yapis Merauke with a tcount of 1.742 and a sig of 0.001. Attitude has an influence on student achievement in junior high school (SMP) Yapis Merauke with a tcount of 1.742 and a sig of 0.001. Attitude variable h , ,, .